Analysts’ Forecast Properties, Political Connection and Corporate Governance: Evidence from Saudi Arabia - Alqahtani, Abdulaziz Saad J (Curtin University, 2023)
This study examines the impact of political connections on analyst forecast activities, namely, analysts’ forecast accuracy, analysts’ forecast dispersion and analysts’ following. Further, this study investigates the association between analysts’ forecast activities and corporate governance attributes: institutional ownership, the board size, board independence and audit committee independence. Next, this study explores corporate governance's role in mitigating political connections' impact on analysts’ forecast activities.